Legal framing for achieving ‘good ecological status’ for Malaysian rivers: are there lessons to be learned from the EU water framework directive? - Md Khalid, Rasyikah; Mokhtar, Mazlin B.; Jalil, Faridah; Ab Rahman, Suhaimi; Spray, Christopher (Elsevier, 2018)
River degradation and loss of ecosystem services due to pollution and deforestation poses a great challenge for a holistic and sustainable river basin management. In Malaysia, about two third of its rivers are categorized as slightly polluted or polluted and this has led to the loss of ecosystem services in many of its river basins, notably in the rapidly developed Langat River Basin. The general historic legal responses to pollution control like water quality standards and gazettal of protected areas seems to rectify the problem as it occurs but is unsustainable. In other parts of the world, there has been a rise in alternative framings of river basin management like the Ecosystem Services Approach (ESA), integrated river basin management (IRBM), catchment based and stakeholder led river management; and these are seen as one way forward for sustainable basin management. The aim of this paper is to explore whether such framings can be implemented in Malaysia based on the current legal and federalism framework. It identifies the major causes and drivers of the polluted and poor state of Langat River and its tributaries and how might an alternative approach improve the situation. Towards this end, a comparative analysis is made with the EU Water Framework Directive (WFD) and its implementation in the Tweed UNESCO HELP basin. Particularly, it explores the application of the subsidiarity principle that allows decision making to be made by agencies closest to the problem within the basin. It concludes that redefining the role of levels of government in IRBM and stakeholder engagement can speed up the process of reframing the Langat IRBM to reduce river pollution and enhance the ecosystem services of the basin.